Surrogate modelling approach: A solution to oil rim production optimization. Issue 1 (1st January 2019) - Aladeitan, Yetunde M.; Arinkoola, Akeem O.; Udebhulu, Okhiria D.; Ogbe, David O.
Abstract: Production from thin oil rim reservoirs can be very challenging due to the thin spread of the oil resources, complicated mechanism of production and fluid contact movement. Typically, the recovery from these types of reservoirs is usually low thereby making them economically unattractive. The objective of this present study is to evaluate the optimal well design for improved recovery from thin oil rim reservoirs. A surrogate modelling approach was deployed for evaluating three different development strategies. Numerical reservoir simulations were conducted to define the basis for the surrogate modelling. In all these strategies, the rim height, reservoir anisotropy, oil viscosity, horizontal permeability, bottom-hole pressure (BHP) and horizontal well length were considered as uncertainty. The selection of the best strategy was based on cumulative hydrocarbon recovery after 30 years of simulation. Uncertainty quantification was achieved using regular Monte Carlo Simulation. Management of a wide range of subsurface uncertainties was considered. The results showed that placing the well just above the oil-water contact (OWC) allowed more oil recovery compared to other strategies considered in this study. The results derived from surrogate model predictions compared favourably with those observed from the YADD thin oil rim reservoirs located in the Niger Delta. The methodology adopted saves time and is reproducible where oil rim development is desirable.